The archaeology of medieval Islamic frontiers: from the Mediterranean to the Caspian Sea - Eger, A. Asa, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2019)
Different areas of the Islamic polity previously understood as "minor frontiers" were in fact of substantial importance to ancient state formation. Exploring different concepts of "border" in areas whose importance previously went unrecognized, including Maghreb, the Mediterranean, Egypt, Nubia, and the Caucasus through archaeological and documentary evidence.--Provided by publisher.
The archaeology of medieval Islamic frontiers: an introduction / Asa Eger -- The western frontiers: the Maghrib and Mediterranean Sea -- Ibadi boundaries and defense in the Jabal Nafūsah (Libya) / Anthony J. Lauricella -- Guarding a well-ordered space on a Mediterranean island / Renata Holod and Tarek Kahlaoui -- Conceptualizing the Islamic-Byzantine maritime frontier / Ian Randall -- The southern frontiers: Egypt and Nubia -- Monetization across the Nubian border: a hypothetical model / Giovanni R. Ruffini -- The land of Tari' and some new thoughts on its location / Jana Eger -- The Eastern frontiers: the Caucasus and Central Asia -- Overlapping social and political boundaries: borders of the Sasanian Empire and the Muslim Caliphate in the Caucasus / Karim Alizadeh -- Buddhism on the shores of the Black Sea: the North Caucasus frontier between the Muslims, Byzantines, and the Khazars / Tasha Vorderstrasse -- Making worlds at the edge of everywhere: politics of place in late medieval Armenia / Kathryn J. Franklin.
Keywords: Islamic Empire -- Antiquities; Islamic Empire -- Boundaries; Borderlands -- Islamic Empire